1995
DOI: 10.1006/viro.1995.1326
|View full text |Cite
|
Sign up to set email alerts
|

An Arbovirus Cline across the Northern Hemisphere

Abstract: The mode and tempo of arbovirus evolution and dispersal can help to explain the dynamics of pandemics, viral outbreaks, and emerging viruses. By comparing nucleotide and deduced amino acid sequences of their envelope proteins, we describe the continuous distribution of the tick-borne encephalitis (TBE) complex viruses, the most important flaviviruses in Europe, across major geographical areas and the conditions under which mutations occur. The analyses reveal a correlation between the geographical and genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 0 publications
11
90
1
3
Order By: Relevance
“…The mosaic character of the distribution of FE-TBEV isolates in non-FE-TBEV-endemic territories is not in agreement with the hypothesis of continuous evolution of TBEV and its persistent expansion into new geographical regions (Zanotto et al, 1995). It is very unlikely that the parallel and similar evolution of TBEVs occurred in restricted geographical areas, and we suggest that FE-TBEV foci appeared in the non-endemic regions relatively recently.…”
contrasting
confidence: 88%
“…The mosaic character of the distribution of FE-TBEV isolates in non-FE-TBEV-endemic territories is not in agreement with the hypothesis of continuous evolution of TBEV and its persistent expansion into new geographical regions (Zanotto et al, 1995). It is very unlikely that the parallel and similar evolution of TBEVs occurred in restricted geographical areas, and we suggest that FE-TBEV foci appeared in the non-endemic regions relatively recently.…”
contrasting
confidence: 88%
“…The difference among the tick-borne viruses grouping together is quite high suggesting a long evolutionary history in the slow evolutionary process described for viruses in ticks [20,28]. It is of note that UUKV and SFSTV are more closely related to each other than to either BHAV or PALV (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The results obtained by the molecular clock analysis suggested that SLEV is a relatively new flavivirus in comparison with other flaviviruses that are transmitted by mosquitoes, such as dengue virus and yellow fever virus (Zanotto et al, 1995(Zanotto et al, , 1996Bryant et al, 2007), as its evolutionary history was dated between 1875 and 1973 (mean 1898). The analysis conducted by Auguste et al (2009), which included 73 SLEV strains, indicated SLEV dispersal from South America towards North America and is in agreement with the current chronological analysis of the 133 SLEVs performed in this study (Fig.…”
Section: Resultsmentioning
confidence: 99%